New Research on Groen van Prinsterer and the Idea of Sphere Sovereignty - Friesen, J. Glenn (Philosophia reformata, 2019)
Historians of Reformational philosophy often claim that Abraham Kuyper obtained the idea of sovereignty in its own sphere from Guillaume Groen van Prinsterer. But very little historical research has been done on Groen's sources for and development of this idea. The first use of the Dutch phrase souvereiniteit in eigen sfeer is much earlier than previously thought; it was used in 1853 by J.I. Doedes, an associate of the "ethical theologian" Daniël Chantepie de la Saussaye. Groen became aware of the ideas of Franz von Baader through journals founded by them, and by reading and corresponding with them and others, such as J.H. Gunning Jr. and Friedrich Fabri. Groen himself owned some of Baader's books. He also relied strongly on the work of the jurist Friedrich Julius Stahl, who was 37 years younger than Baader but taught for a while at the same Munich university and shared Baader's anti-revolutionary ideas.